Baja visión en paciente masculino de 10 años. - Salcedo León, Ginger Valeria (2023)
Through this clinical case we will discuss the importance of carrying out a vision evaluation from an early age, through these tests the incidence of pathologies that can generate long-term problems can be diagnosed and, in turn, the professional optometrist provides the necessary treatment. The patient under study in this clinical case is 10 years old, male and went to the clinic for a decrease in night vision, the patient has degenerative myopia that had been corrected through the use of aerial lenses. The patient's mother tells us that by applying the glasses with measure the patient's vision improved, however in the last 3 weeks problems have been detected in night vision, the patient has constant accidents at night with the objects around him. The anamnesis was applied where relevant data on family ocular pathologies were identified, the paternal grandmother presents degenerative myopia, the referral to the ophthalmologist is proceeded in order to carry out more in-depth studies to rule out any other novelty. Upon return from the ophthalmological check-up, a stationary congenital night blindness is determined after a thorough analysis. The treatment applied is to correct the graduation of the lenses and preserve the selective filters for low vision.